2017
DOI: 10.1021/acs.joc.7b00830
|View full text |Cite
|
Sign up to set email alerts
|

Nitroalkenes as Latent 1,2-Biselectrophiles – A Multicatalytic Approach for the Synthesis of 1,4-Diketones and Their Application in a Four-Step One-Pot Reaction to Polysubstituted Pyrroles

Abstract: An NHC-catalyzed nitro-Stetter/elimination/Stetter reaction sequence employs nitroalkenes as latent 1,2-dication synthons providing a novel access to highly useful symmetrical and unsymmetrical 2-aryl substituted 1,4-diketone building blocks from commercially available aldehyde precursors. For less activated (aliphatic) aldehydes, a cooperative catalytic strategy has been developed via the merger of NHC and H-bonding catalysis. To further showcase the versatility of our approach, a great variety of these unpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 91 publications
0
19
0
Order By: Relevance
“…In contrast to 1,4‐dicarbonyls in general, the synthesis of 1,4‐diketones poses a greater challenge, often requiring use of an excess of one coupling partner and/or significant pre‐functionalisation of substrates to achieve the desired heterocoupling. Reported methods include oxidative homocoupling [23–27] or heterocoupling of ketone enolates, [7,24,28–34,35,36] alkylation of enolates, [9,14,37–42] alkylation of acyl anion equivalents [43–47] or acyl radicals, [11,48] acylation of homoenolate equivalents, [12,13,49–52] or multicomponent strategies [53,54] . Only a subset of methods have been reported that tolerate aliphatic substrates for both reaction partners: addition of silyl enolates to oxyallyl zwitterions [10] and the aldehyde umpolung‐based Stetter reaction [4,5,45,55] …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to 1,4‐dicarbonyls in general, the synthesis of 1,4‐diketones poses a greater challenge, often requiring use of an excess of one coupling partner and/or significant pre‐functionalisation of substrates to achieve the desired heterocoupling. Reported methods include oxidative homocoupling [23–27] or heterocoupling of ketone enolates, [7,24,28–34,35,36] alkylation of enolates, [9,14,37–42] alkylation of acyl anion equivalents [43–47] or acyl radicals, [11,48] acylation of homoenolate equivalents, [12,13,49–52] or multicomponent strategies [53,54] . Only a subset of methods have been reported that tolerate aliphatic substrates for both reaction partners: addition of silyl enolates to oxyallyl zwitterions [10] and the aldehyde umpolung‐based Stetter reaction [4,5,45,55] …”
Section: Figurementioning
confidence: 99%
“…Reported methods include oxidative homocoupling [23][24][25][26][27] or heterocoupling of ketone enolates, [7,24,[28][29][30][31][32][33][34]35,36] alkylation of enolates, [9,14,[37][38][39][40][41][42] alkylation of acyl anion equivalents [43][44][45][46][47] or acyl radicals, [11,48] acylation of homoenolate equivalents, [12,13,[49][50][51][52] or multicomponent strategies. [53,54] Only a subset of methods have been reported that tolerate aliphatic substrates for both reaction partners: addition of silyl enolates to oxyallyl zwitterions [10] and the aldehyde umpolung-based Stetter reaction. [4,5,45,55] The NHC-catalysed intermolecular Stetter reaction, using N-Bn NHC pre-catalyst 1 and the N-Et (2) and N-Me (3) analogues, inspired by the activity of thiamine [54][55]…”
mentioning
confidence: 99%
“…This microwave-assisted coupling-isomerization reaction (MACIR)-Stetter reaction was accomplished using thiazolium salta 64 (as catalyst) in ethanol using Et N. Then, the produced thienyl- .0]undec-7-ene (DBU) as a base; the chromatographed product was applied without additional identification in the formation of thiophene 67 d. [36] Zeitler and co-worker in 2017 reported a NHC-catalyzed nitro-Stetter/elimination/Stetter reaction sequence using nitroalkenes as latent 1,2-dication synthons to give various symmetrical and unsymmetrical 2-aryl functionalized 1,4-diketone scaffolds from market purchasable or easily accessible aldehyde materials. [37] This reaction was performed in the presence of achiral catalyst 70, and K 2 CO 3 as base in diethyl ether at room temperature. After the addition of aldehyde 68 at 50°C, the corresponding Stetter products 71 were produced and the straightforward conversion of them using amine in HOAc at 70°C provided the corresponding pyrroles 72 a-g (Scheme 14).…”
Section: Intermolecular Stetter Reactionmentioning
confidence: 99%
“…Next, the addition of aldehyde 2 and potassium carbonate at 40 °C gave the corresponding Stetter product 74 . In the following, polysubstituted pyrroles 75 were provided using benzylmine and HOAc at 50 °C [37] . Scheme 15 exhibits the same illustrative instances for each class of groups.…”
Section: Intermolecular Stetter Reactionmentioning
confidence: 99%
“…Then, aldehyde (0.25 mmol) was added and the reaction mixture stirred at 50 °C for 7 h. The results shown that by (100 mol %) of base K 2 CO 3 and in the Et 2 O, the desired product (3) with the best yield Is obtained and in other cases, two by‐products were produced (Scheme ). After reach to optimum conditions for this step, amine (0.75 mmol) and acetic acid (2 ml) was added to the reaction mixture and was stirred for the 1.5 days at 70 °C to produce polysubstituted pyrroles (Scheme ) …”
Section: Synthesis Of Pyrrole Derivatives By β‐Nitrostyrene Via Multimentioning
confidence: 99%